Marta Minujín - arte! arte! arte! - Alexander, M. Darsie; Alonso, Rodrigo (Jewish Museum, 2023)
The monograph presents two hundred paintings, sculptures and works on paper, as well as performance documentation and multimedia works. This handsome volume is published on the occasion of the exhibition organized by the Jewish Museum, New York, on the work and historical context of the Argentinian artist Marta Minujín (b. 1943), a central figure in the Latin American avant-garde. This heavily illustrated, beautifully designed monograph provides a overview of her career, traces intersections with American, European and Latin American developments in postwar art, and explores her contemporary relevance to the next generation of artists. This publication includes a major critical essay, "Arte! Arte! Arte! The Immersive World of Marta Minujín," by Darsie Alexander, chief curator at the Jewish Museum, surveying Minujín’s art, practice, and influence; a second essay, "Rise Up and Live!", by the Argentinian journalist and curator Rodrigo Alonso, places Minujín in the political and historical context of Argentina in the years from the dictatorship of Juan Perón to the restoration of democracy and after. The book concludes with an interview with Minujín, "Art Protects Me," focusing on the artworks she created during the Covid pandemic of 2020–21. The volume is illustrated extensively throughout with Minujín’s artworks, her performance pieces and happenings, large-scale public works, and images of her at work. Initially positioned as Argentina’s "answer to Pop art," Marta Minujín remains a genre-defying artist who has produced some of the most experimental work of her generation. Extraordinarily versatile, Minujín’s career has traversed major developments in postwar art while maintaining a singular vision and aesthetic
Impressum: This book has been published in conjunction with the exhibition "Marta Minujín: Arte! Arte! Arte!", Jewish Museum, New York, November 17, 2023 - March 31, 2024
Keywords: Minujin, Marta -- 1943-; Ausstellungskatalog -- Jewish Museum -- 17.11.2023-31.03.2024 -- New York, NY